2016
DOI: 10.1016/j.childyouth.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Promoting birth parents' relationships with their toddlers upon reunification: Results from Promoting First Relationships® home visiting program

Abstract: Birth parents, once reunified with their child after a foster care placement, are in need of in-home support services to prevent reoccurrence of maltreatment and reentry into foster care, establish a strong relationship with their child, and enhance child well-being. Few studies have addressed the efficacy of home visiting services for reunified birth parents of toddlers. This study reports on the findings from a randomized control trial of a 10-week home visiting program, Promoting First Relationships® (Kelly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 48 publications
4
35
0
Order By: Relevance
“…First, the sample is small, and replication regarding both child and parent outcomes are required. Moreover, larger samples would also allow testing for potential moderators, some of which have already been mentioned in the attachment intervention literature, most notably child age (Moss et al, 2011), social services characteristics (Oxford et al, 2016), and genetic polymorphisms that would allow for an examination of differential susceptibility to intervention. Such information is important for determining the suitability of the intervention program for different populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the sample is small, and replication regarding both child and parent outcomes are required. Moreover, larger samples would also allow testing for potential moderators, some of which have already been mentioned in the attachment intervention literature, most notably child age (Moss et al, 2011), social services characteristics (Oxford et al, 2016), and genetic polymorphisms that would allow for an examination of differential susceptibility to intervention. Such information is important for determining the suitability of the intervention program for different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas few studies have showed a decrease in parenting stress and psychological distress from pre-to posttreatment (Thomas & Zimmer-Gembeck, 2011;Timmer, Urquiza, Zebell, & McGrath, 2005;Timmer, Ware, Urquiza, & Zebell 2010), a recent meta-analysis of parenting programs implemented in maltreatment samples found a nonsignificant intervention effect on parenting stress (Chen & Chan, 2016). More surprising, recent findings by Oxford, Marcenko, Fleming, Lohr, and Spieker (2016) documented increases in parental stress following exposure to an attachment-based intervention strategy. Empirical findings testing how subjective experiences of stress relate to intervention exposure are therefore unclear.…”
Section: Parental Stressmentioning
confidence: 97%
“…Although these findings would be the hypothesized outcome of a parent training intervention, they are novel because, to our knowledge, no existing studies have examined in-home parent training interventions that were delivered to biological families of children and adolescents in foster care. In fact, among the randomized studies identified in our review of parent training interventions delivered to families involved in child welfare, none included children over the age 12 (Bernard et al, 2012; Chaffin et al, 2004, 2011; Chamberlain et al, 2008; DeGarmo et al, 2013; Dozier et al, 2008; Linares et al, 2006; Oxford et al, 2016; Price et al, 2008, 2015). Additionally, other studies of parent training interventions with child welfare populations have seen child behavior problems change in the direction expected but have failed to demonstrate main effects of the intervention on child problem behaviors at posttest (DeGarmo et al, 2013; Linares et al, 2006; Oxford et al, 2016).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…Despite efforts to expand and rigorously evaluate research-supported parenting interventions among children in foster care, most randomized studies have investigated interventions that targeted: (1) foster parents (Dozier, Peloso, Lewis, Laurenceau, & Levine, 2008; Leve et al, 2012; Mersky, Topitzes, Grant-Savela, Brondino, & McNeil, 2016; Price et al, 2008), (2) biological parents who were selected with various criteria but may or may not have had their children in foster care (e.g., confirmed physical abuse, involvement with head start and a history of child welfare reports; Bernard et al, 2012; Chaffin, Funderburk, Bard, Valle, & Gurwitch, 2011; Chaffin et al, 2004; Hurlburt, Nguyen, Reid, Webster-Stratton, & Zhang, 2013), or (3) biological parents whose children had already reunified with them (DeGarmo, Reid, Fetrow, Fisher, & Antoine, 2013; Oxford, Marcenko, Fleming, Lohr, & Spieker, 2016). Indeed, few parenting interventions have been tested with biological parents while their children were still in foster care (Linares, Montalto, Li, & Oza, 2006).…”
mentioning
confidence: 99%
“…The trial’s results indicated that PFR increased caregiver sensitivity and knowledge of child development (Spieker et al 2012) and improved permanency for those children who received the program while with a foster or kin caregiver (Spieker et al 2014). Evidence of some additional positive intervention effects were found among the subsample of reunified birth parents (Oxford et al 2013, 2016a). In a small pilot study within FFP, children in the PFR condition showed an improvement in cortisol response relative to the control group (Nelson and Spieker 2013).…”
Section: Introductionmentioning
confidence: 96%